Czy osoba z zespołem Downa może ważnie zawrzeć małżeństwo w Kościele katolickim? - Nowicka, Urszula (Ius Matrimoniale, 2017)
Down syndrome is a genetic disorder caused by the presence of all or part of a third copy of chromosome 21. Those with Down syndrome nearly always have physical and intellectual disabilities. For a possible marriage is the most important, that this defect is often accompanied by other diseases that have a smaller or greater impact on the lives of people with Down sindrome and their families. Among them are often mild or moderate mental retardation. Therefore, the question arises as to whether a persons with Down syndrome can celebrated validity marriage in the Catholic Church and what aspects must be taken into account when considering their legal situation.